The Effectiveness of Jigsaw Reading and Think-Pair Share in Improving Studentsâ Vocabulary Mastery - Febriyanti, Febriyanti (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
This study is aimed to find out which technique is better in improving studentsâ vocabulary mastery. The techniques used in this research are Jigsaw Reading and Think-Pair Share. This is a quantitative research with quasi experiment design. The researcher took two classes to apply those techniques. After conducting the treatments for four meetings, the students of each group are given the vocabulary test. The data were analyzed by using t-test with SPSS program. The result showed that Think-Pair Share is better than Jigsaw Reading to apply in the classroom to improve the studentsâ vocabulary mastery.